Sosialisasi Pariwisata Halal dan Pendampingan Sertifikasi Halal Bagi Pelaku UMKM di Desa Sintung Peringgarata Lombok Tengah - Syarihudin, Moh.; Supardi, Supardi (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
One of the most important aspects of the halal tourism ecosystem is halal food and beverages. For a Muslim, halal is not only a trend but also a necessity, a religious commandment, and a legal mandate. The state guarantees the freedom of its citizens to embrace and carry out religious orders according to their respective beliefs. For this reason, the state guarantees halal products for the Muslim community. The implementation of this is the obligation of halal certification of food and beverage products and goods in circulation both from large companies and MSMEs. Therefore, it is necessary to hold a seminar and mentoring activities to educate and assist business actors regarding the halal product process to halal certification, especially in tourist villages. This seminar activity used lectures, interactive dialogue, and mentoring methods related to halal tourism and certification. This activity took place in Sintung village, Peringgaarata sub-district, Central Lombok district. The participants are the community, business actors, and government elements. This activity was carried out using lectures, question-and-answer discussions, and mentoring. The results of this activity are; first, increasing public understanding of halal tourism. Second, increasing awareness to take care of halal certification by MSME players. Third, there is less difficulty in taking care of halal certification.